Endothelial Reprogramming in Sports Traumatology: Role of the Widespread Neuro-Immuno-Endocrine-Endothelial System - Vincenzo Cristian Francavilla; Omar Mingrino; Donatella Di Corrado; Maria Bellomo; Giuseppe Lanza; Caterina Crescimanno; Francesca Orofino; Maria Chiara Parisi (Applied Sciences, 2022)
This paper deals with the role of the widespread neuro-immuno-endocrine-endothelial system in sport traumatology. The aim of this work is to see if sport or regular physical activity is able to reprogram the endothelium, to advance the new concept of neuro-immuno-endocrine-endothelial diffused system, and to introduce in the practice of sport medicine a new test in the fields of “Athlete functional evaluation” and “Sports fitness”. The first object of this paper is to see whether sport or regular physical activity can change the functional structure of the endothelium. The second goal is to frame under a general view the knowledge and individual lines of research on endothelium, to highlight what we believe is, in the organization of homeostasis, the location of this ‘organ’, namely in the neuro-immune-endocrine system spread.